Analisis Kestabilan Lereng Pada Relokasi Jalan di Bendungan Bulango Ulu, Kabupaten Bone Bolango, Provinsi Gorontalo - Alya Rahmawati Panai; Muh Kasim; Ronal Hutagalung (Universitas Negeri Gorontalo, 2026)
This study aims to evaluate slope stability along the relocated road section of Bulango Ulu Dam, Bone Bolango Regency, Gorontalo Province. The research focuses on geological conditions, rock mass quality, and slope stability using Rock Mass Rating (RMR) and Slope Mass Rating (SMR) methods based on scanline mapping data. Field investigations were conducted on four slope segments (AP1–AP4) by measuring discontinuity characteristics, rock strength, spacing, and groundwater conditions.The results indicate that the rock mass quality of all slope segments falls into Class I–II of the RMR system, categorized as very good to good rock, with RMR values ranging from 70 to 83. SMR analysis shows that all slope segments belong to Class II, indicating stable slope conditions. Kinematic analysis reveals that the dominant potential failure mechanism is toppling failure, with probability of failure values ranging from 10.00% to 23.97%.Although the slopes are classified as stable, the presence of geological structures, particularly discontinuities, contributes to potential instability under certain conditions. Continuous monitoring is therefore recommended to mitigate future landslide risks. The findings provide important insights for slope stability evaluation and infrastructure safety planning in mountainous regions.